Acquired pellicle engineering for the control of dental erosion: evaluation of the protective potential of statherin - Taira, Éven Akemi (2022)
This thesis was divided into 3 manuscripts. In the first stage of the first study, the influence of serine phosphorylation on the degree of protection against dental erosion in vitro, provided by peptides statherin-derived from, was evaluated. 105 bovine enamel blocks were divided into 6 groups: 1) StatSS; 2) StatpSS; 3) StatSpS; 4) StatpSpS; 5) Recombinant human statherin and 6) Phosphate Buffer. In the second stage of the first study, different concentrations of the peptide with the best results in the first stage were evaluated, in the protection against dental erosion. 105 bovine enamel blocks were divided into 6 groups: 1) CaneCPI-5 0.1 mg/mL, 2) Phosphate Buffer; 2) StatpSpS 0.94×10-5 M; 3) StatpSpS at 1.88×10-5 M; 4) StatpSpS 3.76×10-5 M; 5) StatpSpS 7.52×10-5 M. The treatments were carried out for 2h at 37°C, under agitation. Stimulated saliva was collected from 3 volunteers to form the acquired pellicle (AP) (2h) on the specimens. Erosive challenge was performed by treatment with 0.01M HCl for 10s at 37ºC, under agitation, 1X/day for 3 days. The % change in surface hardness (%SHC) was calculated. In step 1, only the peptide with phosphorylated serines 2 and 3 (StatpSpS) significantly reduced the %SHC compared to the negative control. In step 2, only StatpSpS at a concentration of 1.88X10-5 M significantly reduced the %SHC in relation to negative and positive controls, after 3 days of treatment. In the second study, the experiments were performed on 4 consecutive days. On each day, the volunteers (n=9), after prophylaxis, rinsed their mouths with 10 mL of phosphate buffer alone or containing 1.88X10-5 M StatpSpS. The acquired pellicle (AP) was formed on the enamel for 3 or 120 min. Subsequently, the pellicle was removed with filter paper, soaked in 3% citric acid. Proteins were extracted and subjected to reversed-phase liquid chromatography coupled to a mass spectrometer (nLC-ESI-MS/MS). In both periods evaluated, treatment with StatpSpS profoundly altered the proteomic profile of the AP, which impacts on the protection against demineralization. In the third study, performed in situ, 180 specimens of bovine enamel and dentin were divided into: Erosion (n=90) and Erosion+Abrasion (n=90) conditions. The study had 3 crossover phases (n=30/phase), according to the treatments: 1.88X10-5 StatpSpS solution; commercial solution containing SnCl2/NaF/AmF (Elmex Erosion); deionized water. 15 volunteers wore a palatal appliance for 5 days in each phase. Erosive challenges were performed 4x/day with 0.01 M HCl for 1 min, followed or not by an abrasive challenge (electric brush and toothpaste slurry, 15 s, 2x/day). Wear evaluation was performed by contact profilometry. For both substrates, there was no significant difference between the conditions, but there was a significant difference among the treatments. The lowest wear was found for the commercial solution Elmex and for the solution containing StapSpS, which did not differ significantly from each other, but both showed greater protection when compared to the negative control. StatpSpS has great potential to be inserted into dental products, aiming to protect against dental erosion, through procedures involving AP engineering.